Pathways from information to the adoption of conservation agriculture practices in Malawi and Tanzania - Marenya, Paswel P.; Gatua, Josephine G.; Rahut, Dil B. (Cambridge University Press, 2023)
To reduce agriculture's carbon, land and water footprint, the diffusion of conservation farming methods is one commonly cited proposition. Yet the process of translating available information on new conservation farming methods into farmers' practices is often a black box in many studies. This understanding is critical to inform strategies for scaling these complex, knowledge-intensive, but necessary practices for improving agriculture's resource and climate balance sheet. By implementing a series of mediation analysis using data from 700 households in Malawi and 930 households in Tanzania, this study examines how an improved understanding of conservation agriculture (CA) principles is an important mediator in the pathway from extension contact to the adoption of two of the CA practices examined. For the adoption of conservation tillage, the share of the mediated treatment effect was in the 31.5–34.4% range, while it was 31.6–46.9% for the adoption of soil cover (mulching). Our results suggest that unless learning from external sources strongly correlates with improved farmers' technical understanding of new farming practices, private learning by doing must be a critical adjunct to other avenues of learning. Beyond the basic promotional goals, improving farmers' technical know-how needs to be the centerpiece of holistic efforts in support of conservation farming and similar knowledge-intensive practices necessary for agriculture's sustinability goals.